LEGAL FRAGILITY OF PERUVIAN CRIMINAL LAW ON QUALIFICATIONS BASED ON RESULT - Montellanos Murillo, Diego Alonso (2026)
For the first time, the issue of aggravated offenses based on their outcome is addressed comprehensively and in a complete compilation within the legal-penal sphere. This research finds its purpose in analyzing the most significant positions formulated by Peruvian legal scholars on offenses aggravated by their outcome, both past and present. In this exercise, in order to clarify the current status of the treatment of these legal concepts, various theoretical formulations were compared, revealing deficiencies related to their academic inclusion and the clarity of their analysis. Both of these shortcomings stem from interpretive errors that contravene current criminal law axiologically and normatively: conceptual and exegetical confusions, and violations of the principles of legality, culpability, and the exceptional nature of punishment for negligence. As expected, academic criticism underscores the position defended here.